2010
DOI: 10.1371/journal.pgen.1000948
|View full text |Cite
|
Sign up to set email alerts
|

Defective Resection at DNA Double-Strand Breaks Leads to De Novo Telomere Formation and Enhances Gene Targeting

Abstract: The formation of single-stranded DNA (ssDNA) at double-strand break (DSB) ends is essential in repair by homologous recombination and is mediated by DNA helicases and nucleases. Here we estimated the length of ssDNA generated during DSB repair and analyzed the consequences of elimination of processive resection pathways mediated by Sgs1 helicase and Exo1 nuclease on DSB repair fidelity. In wild-type cells during allelic gene conversion, an average of 2–4 kb of ssDNA accumulates at each side of the break. Longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
178
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(196 citation statements)
references
References 56 publications
14
178
4
Order By: Relevance
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).Both the extensive lengths and high abundance of bidirectional noncrossover tracts we observed can be explained if these tracts result not from canonical DSBR but from dBIR. The dBIR mechanism is also a better fit for our experimental system in which replication stress is likely to result in replication fork 124 S. A. Chumki et al…”
mentioning
confidence: 86%
“…Subsequent work revealed that these assays largely overestimated the length of DNA that is resected in vivo under normal conditions when repair is possible. In mitotic cells, it has been determined that ϳ2,000 -4,000 nt are resected in allelic recombination and ϳ3,000 -6,000 nt are resected in ectopic recombination (38). In meiotic cells, where the long-range resection is largely dependent on Exo1, the resection tracks are even shorter (ϳ800 nt) (39).…”
Section: Rad51-dependent Pathwaymentioning
confidence: 99%
“…In yeast, Pif1 helicase is suggested to be involved in mitochondrial DNA recombination, repair, and replication (6,11). Some of its nuclear functions include Okazaki fragment processing (12,13), inhibition of rDNA replication (14), unwinding of G-quadruplex structures (15)(16)(17)(18), telomere regulation (19 -21), and repair of double-stranded DNA breaks (22)(23)(24)(25). S. cerevisiae Pif1 belongs to the superfamily (SF) 2 1B class of helicases.…”
mentioning
confidence: 99%